Problem-solving ability: Implementation of RICOSRE learning models on environmental change topic - Eka Putri Azrai; Erna Heryanti; Ammar Zain; Pratiwi Ningsih (University of Muhammadiyah Malang, 2022)
The development of technology and science has progressed very rapidly. Students are required to master various kinds of abilities, one of which is problem-solving ability. Problem-solving ability need to be developed in the learning process. The learning model that can facilitate students in practicing problem-solving ability is the Reading, Identifying, Constructing, Solving, Reviewing and Extending (RICOSRE) learning model. The purpose of this study was to determine the effect of using the RICOSRE learning model to the problem-solving abilities of Senior high school students on environmental change topic. This research was conducted at Senior High School 3 of Tangerang in January-June 2022. This type of research is quantitative with a quasi-experimental research method. The research sample amounted to 62 students with each class totaling 31 students who were selected by random sampling. Based on the t-test calculation at α = 0.05, a significance of 0.028 was obtained, which means that there is an effect of the RICOSRE learning model on the problem-solving abilities of students on environmental change topic.